The relationship between communication satisfaction and teachers` job satisfaction in the Malaysian primary school - Abdullah, Zulhamri; Hui, Jong (Asian Journal of Humanities and Social Sciences, 2014)
The purpose of this study is to identify the relationship between communication satisfaction and job satisfaction among the primary school teachers. The model of Communication Satisfaction Questionnaire which developed by Downs and Hazen in 1977 is used in this study to examine the relationships. 226 survey questionnaires were completed by primary school teachers from Johor, Malaysia. The main finding shows there is a small but significant positive relationship between communication satisfaction and job satisfaction. There is still a necessity for school management to develop good quality communication environment for teachers in order to improve job performance even though the influence or effects of communication satisfaction on teacher’s job satisfaction is small or almost negligible.